P411 Genus specific real-time PCR-a promising technique for rapid diagnosis of fungal keratitis. (20th September 2022) - Tawde, Yamini; Das, Sourav; Singh, Shreya; Sharma, Savitri; Gupta, Amit; Basak, Soham; Shrimali, Twishi; Rudramurthy, Shivaprakash M.; Kaur, Harsimran; Chakrabarti, Arunaloke; Ghosh, Anup
Abstract: Poster session 3, September 23, 2022, 12:30 PM - 1:30 PM: Objective: Comparison of different existing molecular methods for diagnosis of fungal keratitis (FK) and to develop and validate genus-specific PCR for identification of most predominant FK causative agents. Method: A prospective multicentric study was performed between November 2019 to August 2021 from four centers across India. Corneal tissue/scraping samples were collected from patients with suspected keratitis for preliminary microbiological workup at respective centers and molecular diagnosis at the Postgraduate Institute of Medical Education and Research (PGIMER), Chandigarh. A total of 87 corneal button samples were used for standardization. All samples were subjected to DNA extraction followed by molecular diagnosis using pan-fungal primers by conventional PCR, semi-nested PCR, and real-time PCR targeting the internal transcribed spacer (ITS) region of rDNA. The genus-specific primers for the most common causative agents of FK ( Aspergillus sp., Fusarium sp., Alternaria sp., and Curvularia sp.) were designed in ITS2 region and standardized for real-time PCR. The best performing protocol was validated in 145 corneal samples. Result: A total of 68 patients out of 87 were diagnosed with FK of which 91.17% ( n = 62/68) were microscopy positive and 82.3% ( n = 56/68) were culture positive. Among the culture positive, the most common isolate was Aspergillus sp. (26, 46.42%) followed by Fusarium sp. (21, 37.5%) while the remaining samples grew dematiaceous fungi. Real-time PCR targeting ITS2 region proved to be most sensitive (52.94%) and specific (84.21%) compared with conventional PCR and semi-nested PCR. Genus-specific real-time PCR for Aspergillus sp. and Fusarium sp. showed improved sensitivity and specificity of 82.76%, 87.18%, and 90.91%, 93.48% respectively compared with all other diagnostic methods used in the study. The positive (PPV) and negative predictive value (NPV) for Aspergillus sp. specific PCR were 82.76% and 87.18% while Fusarium sp. specific PCR showed PPV of 86.96% and NPV of 95.56%. Genus-specific real-time PCRs did not show any amplification of 19 FK negative samples while faint amplification was observed in conventional PCR which on sequencing proved to be non-specific. No cross-reactivity was observed in clinical sample standardization. Due to the lack of Alternaria sp. and Curvularia sp. positive clinical samples, both PCRs were standardized using respective culture DNA which showed a positive result. Aspergillus sp. and Fusarium sp. genus-specific PCRs were further validated in 145 corneal samples, of which 91 were FK positive and showed similar results as that of standardization data. Genus-specific PCRs also reduced the turnaround time (˂24 h) by decreasing the need for the identification of causative agents. Conclusion: Real-time PCR targeting ITS 2-region, particularly the genus-specific PCRs proved to be the most efficient for molecular diagnosis of FK. The genus-specific PCRs reduce the turnaround time by avoiding the need for sequencing and thus facilitating in rapid diagnosis of FK.